2023
DOI: 10.2147/jir.s430831
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Value of Neutrophil to Lymphocyte Ratio in Gouty Arthritis: A Narrative Review

Yiming Chen,
Jian Liu,
Yang Li
et al.

Abstract: Since the incidence of gouty arthritis (GA) exhibits yearly increases, accurate assessment and early treatment have significant values for improving disease conditions and monitoring prognosis. Neutrophil to lymphocyte ratio (NLR) is a common indicator in blood routine, which has the characteristics of easy access and low cost. In recent years, NLR has been proven to be an effective indicator for guiding the diagnosis, treatment, and prognosis of various diseases. Moreover, NLR has varying degrees of relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…The results showed significant improvements in these inflammatory markers among patients consuming alkaline water compared to the control group, especially in levels of CRP and IL-1β. [ 18 ] This finding supports the hypothesis that alkaline water alleviates the inflammatory response in gouty arthritis. The potential mechanism may involve alkaline water altering the intra- and extracellular environment through an increase in bodily fluid pH.…”
Section: Discussion and Analysissupporting
confidence: 82%
“…The results showed significant improvements in these inflammatory markers among patients consuming alkaline water compared to the control group, especially in levels of CRP and IL-1β. [ 18 ] This finding supports the hypothesis that alkaline water alleviates the inflammatory response in gouty arthritis. The potential mechanism may involve alkaline water altering the intra- and extracellular environment through an increase in bodily fluid pH.…”
Section: Discussion and Analysissupporting
confidence: 82%
“…The role of inflammation in the development of T2DM and associated metabolic disorders has garnered significant attention [ 11 , 12 ]. In recent years, the NLR has been increasingly studied as a composite biomarker that better reflects the systemic inflammatory state compared to individual biomarkers, being cost-effective and easy to detect [ 13 – 15 ]. NLR has been reported as a reliable inflammatory marker in type 2 DM [ 16 ] and other inflammatory conditions including gastrointestinal diseases [ 17 ], cardiac conditions [ 18 ], thyroiditis [ 19 ], thyroid conditions [ 20 ], irritable bowel disease [ 21 ], and Covid-19 infection [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 NLR is defined as the ratio of the absolute number of neutrophils to the absolute number of lymphocytes in blood routine, which dynamically reflects the relative relationship between neutrophils and lymphocytes, thus suggesting inflammatory changes in patients. 40 Some researchers 41 found that NLR was higher in GA patients compared to healthy adults and that NLR was positively correlated with ESR and CRP, suggesting the ability of NLR to assess the disease activity of GA. In this study, we found that HQC effectively reduced NLR in GA patients, indicating that HQC may contribute to repressing immune inflammatory reactions in GA. Further animal and cellular experiments are warranted to validate the pharmacological effects and therapeutic mechanisms of HQC in GA.…”
mentioning
confidence: 99%